Variation in Payment Rates under Medicare's Inpatient Prospective Payment System. (8th April 2016) - Krinsky, Sam; Ryan, Andrew M.; Mijanovich, Tod; Blustein, Jan
Abstract : Objective: To measure variation in payment rates under Medicare's Inpatient Prospective Payment System (IPPS) and identify the main payment adjustments that drive variation. Data Sources/Study Setting: Medicare cost reports for all Medicare‐certified hospitals, 1987–2013, and Dartmouth Atlas geographic files. Study Design: We measure the Medicare payment rate as a hospital's total acute inpatient Medicare Part A payment, divided by the standard IPPS payment for its geographic area. We assess variation using several measures, both within local markets and nationally. We perform a factor decomposition to identify the share of variation attributable to specific adjustments. We also describe the characteristics of hospitals receiving different payment rates and evaluate changes in the magnitude of the main adjustments over time. Data Collection/Extraction Methods: Data downloaded from the Centers for Medicare and Medicaid Services, the National Bureau of Economic Research, and the Dartmouth Atlas. Principal Findings: In 2013, Medicare paid for acute inpatient discharges at a rate 31 percent above the IPPS base. For the top 10 percent of discharges, the mean rate was double the IPPS base. Variations were driven by adjustments for medical education and care to low‐income populations. The magnitude of variation has increased over time. Conclusions: Adjustments are a large and growing share of Medicare hospital payments, and they create significant variation in payment rates.